Epigenetic impact of the parents' physical activity on the health of their children - AGNIESZKA BORON (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
All parents' dream is to have healthy children. The question whether the parents' lifestyle affects the quality of their progeny's health has been bothering scientists and society for many years. Based on epidemiological studies, it has been shown that physical activity during pregnancy is beneficial both for the health of the mother and the newborn. A significant number of studies conducted so far have shown that exercises performed by fathers modulate future generations by affecting the sperm epigenome. Epigenetics plays a key role in transmitting the response of the parents' environment and their lifestyle onto the characteristics and health of their progeny.